Wednesday

April 23, 2014

April 23, 2014

Posted by **michelle** on Wednesday, June 13, 2007 at 9:17pm.

(1+sec(beta))/(sec(beta))=(sin^2(beta))/(1-cos(beta))

on the right, sin^2 = 1-cos^2, that factor to 1-cos * `1+cos, then the denominator makes the entire right side 1+cosB

which is 1+1/sec which is 1/sec (sec+1)

qed

using sec(beta) = 1/cos(beta):

1+sec(beta))/(sec(beta))= 1 + cos(beta)

sin^2(beta)/(1-cos(beta)) =

(1-cos^2(beta))/(1-cos(beta)) =

1 + cos(beta)

This follows e.g. from:

(1 - x^2) = (1 - x)(1 + x)

and thus:

(1 - x^2)/(1 - x) = 1 + x

- math -
**rahul**, Thursday, April 25, 2013 at 11:54pmx=(-1)

**Related Questions**

trig - verify the identity: sec(beta)+ tan (beta)= cos(beta)/ 1-sin(beta)

Trigonometry - Prove that tan (Beta) sin (Beta) + cos (Beta) = sec (Beta) Please...

maths - prove that the length of the perpendicular from the origin to the ...

trig - Given sin a = 15/17 with a in Quadrant I and cos beta = 4/5 with beta in ...

pre calc - suppose beta is an angle in the second quadrant and tan beta=-2. ...

Math - Calculus - The identity below is significant because it relates 3 ...

Physics Important please - A yo-yo of mass m rests on the floor (the static ...

Physics Important please - A yo-yo of mass m rests on the floor (the static ...

Physics Important please - A yo-yo of mass m rests on the floor (the static ...

Physics Important please - A yo-yo of mass m rests on the floor (the static ...